Analisis Model Bisnis dengan Pendekatan Business Model Canvas (BMC) dan Analisis SWOT (Studi Kasus Rumah Kayu Bordir) - Rehin, Syafiq Dzakwan; Farah Alfanur (IPM2KPE, 2025)
Rumah Kayu Bordir is a manufacturing company established in 2000 in Jakarta. Rumah Kayu Bordir is now located in Tasikmalaya City. The owner of Rumah Kayu Bordir was struggling to choose the right strategy to address the challenges they faced. Therefore, Rumah Kayu Bordir needed a business model to develop a strategy to address the challenges they faced. The purpose of this study was to propose a new business model for Rumah Kayu Bordir using the Business Model Canvas and a SWOT analysis. The method used in this study was qualitative. Qualitative research is a research method used to examine natural objects. The researcher is the key instrument, data collection is triangulation, and data analysis is inductive. Based on the research results, the current business model for Rumah Kayu Bordir was identified through interviews. Afterward, an in-depth analysis was conducted using SWOT identification. The next step was to design a new business model for Rumah Kayu Bordir. Keywords: Business Model Canvas, SWOT, Business Model, Fashion